AML transformation after autologous stem cell transplant for multiple myeloma. (29th May 2015) - Gupta, Sanjeev Kumar; Chandramohan, Jagan; Kumar, Lalit
Abstract : A 59-year-old male patient was diagnosed as multiple myeloma in 2005 and received chemotherapy consisting of thalidomide, cyclophosphamide, and dexamethasone. The patient subsequently received high-dose melphalan followed by autologous stem cell transplantation and maintenance therapy with thalidomide. During the follow-up, the patient developed fever and cytopenias in 2012. The work up revealed 55% blasts in the marrow with myeloid phenotype leading to a diagnosis of acute myeloma leukaemia (AML). The karyotype was normal (46, XY) on conventional cytogenetics. The therapy was initiated, however, the patient expired within 1 month of diagnosis. The treatment related factors like alkylating agents are usually taken as the responsible agents for therapy-related AML, however, recent studies have proposed a multifactorial pathogenesis of leukaemic transformation in multiple myeloma.